AI-Driven Predictive Maintenance for Transmission Pipes in Oil and Gas Companies - K. Joshi, Manish; Gamit, Vipul; Thakkar, Bhadresh; Kumari, Neha; Koradiya, Nivid; Bhailalbhai, Patel Pratikkumar (Journal of Neonatal Surgery, 2025)
This research study examines the use of AI-based predictive maintenance strategies for oil and gas industry transmission pipes. The study seeks to improve the efficiency and reliability of maintenance activities using AI algorithms for predicting possible breakdowns, maintaining optimal maintenance time, and reducing downtime. Data collection, preprocessing, algorithm choice, implementation, and performance testing are the components of the research methodology. The results prove the success of predictive maintenance using AI to enhance the integrity and lifespan of transmission pipes. This paper ends by stating the advantages of applying AI technologies to maintenance and recommending future studies in this field also how AI may assist in predictive maintenance to maximize the device life.